Electrodeposition of Single Phase SnS Thin Films: Effect of Electrolytic Bath Temperature on the Final Film Properties. Issue 2 (1st January 2019) - Riveros, G.; Ramírez, D.; Gau, Daniel L.; Hernández, L.; Häberle, P.; Marotti, Ricardo E.; Romero, R.; Cuevas, A.; Martín, F.; Dalchiele, Enrique A.
Abstract : In this article, the electrodeposition of single-phase tin monosulfide (SnS) films at different electrolytic bath temperatures is studied. The electrodeposition was carried out potentiostaticaly onto transparent conductive substrates (fluorine-doped tin oxide, and indium tin oxide on a glass substrate) from an acidic solution of SnSO4 and Na2 S2 O3 as tin and sulfur precursors, respectively. The films were characterized through different techniques: field-emission scanning electron microscopy, energy dispersive X-ray analyses, X-ray diffraction measurements, profilometry, Raman spectra, UV-vis measurements, electrochemical impedance spectroscopy and linear sweep photovoltammetry. The films obtained were stoichiometric and no other phases different from SnS were evidenced. A change in the morphology from cubic-like to sheet-like was observed with an increase of bath temperature, which was reflected in the texture coefficient obtained from X-ray diffraction analyses. The bandgap of the films was obtained using a direct absorption edge in the Tauc plots. A decreasing bandgap with electrodeposition temperature was observed, which is attributed to an improvement in the crystallinity of the films. Mott-Schottky plots and linear sweep photovoltammetry measurements confirmed that the films are p-type semiconductors. An increase in the photocurrent of the photoelectrodes was observed with the electrolytic bath temperature, which is attributed to the change of SnS morphology with the electrodeposition temperature.